Effectiveness of Dance Pregnancy Modification on Improving Depression Levels in High-Risk Pregnant Women - Wiwit Vitania; Eftyaningrum Dwi Wahyu Astutik (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to evaluate the effectiveness of Pregnancy Dance modification on improving depression levels and serotonin hormone levels in high-risk pregnant women. The research design used was Quasi Experiment with the Nonequivalent Control Group Design approach. The number of samples in this study was 24 participants, which were divided into two groups: 12 samples of the intervention group and 12 samples of the control group. Based on the Wilcoxon test, the asymp. Sig <0.05 value indicates a significant difference between the pretest and posttest scores, which indicates a positive effect of Pregnancy Dance in reducing depression levels in high-risk pregnant women. After the intervention, there was a greater decrease in depression scores in the Pregnancy Dance group compared to the control group. The control group, which received pregnancy exercise intervention, also experienced a decrease in depression scores with an average decrease of 7.25. However, the analysis showed that the asymp. Sig value 0.000 <0.05, with a greater average decrease in scores in the intervention group than in the control group. In conclusion, although both activities are effective in reducing depression levels, Pregnancy Dance proved to be superior, especially in addressing anxiety and emotional stress, thanks to its more prominent elements of relaxation, body expression and social support.